KAJIAN FUNGSI DAN NILAI MORAL DALAM CERITA ASAL USUL KAMPUNG DI SEKITARAN ISTANA KADRIAH KOTA PONTIANAK - Rahmad Septiadi; Antonius Totok Priyadi; Agus Syahrani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThe background in this study is the function and moral value in the story of the origin of villages at the registered Kadriah Palace Pontianak. The study was intended to examine the function and describe the moral values. The description related due to the implementation in the school. The method used in this study is descriptive method of qualitative research. The source of the data in this study is the story of the origin of villages at the registered Kadriah Palace Pontianak which has four moral values namely (1) relationship between human and God, (2) relationship between human with personal self, (3) relationship between human beings, and (4) relationship between human and nature. The tool of data collection is the researcher himself as the key instrument. The result in this study can be implemented in school in the Indonesian language and literature subject at SMA/MA/SMK grade X (ten) in the odd semester.Keywords: Function, moral, the story of the origin of villages, Istana Kadriah, Pontianak City.